Study and analysis of parallel N-body simulations - Arcencio, Guilherme G.; Guardia, Hélio Crestana (Anais da Escola Regional de Alto Desempenho de São Paulo (ERAD-SP), 2024)
The N-body Problem involves predicting the motion of a group of astronomic particles under the influence of each other’s gravitational field. Due to the nonexistence of closed-form analytical solutions for N bigger than 2, numerical methods must be employed, and those do not scale well for large numbers of bodies. Thus, we developed and investigated parallel, high performance N-body simulations in GPUs and multi-core CPUs, and found that, even with dynamic time steps and synchronization requirements, GPUs massively reduce the time required by the simulations. While multi-core CPUs also allow for large speedups, they are vastly outperformed by the former.